Induction of fungal cellulolytic enzymes using sugarcane bagasse and xylose-rich liquor as substrates - Bordignon, Sidnei Emilio [UNESP] (2020)
Liquor from pretreatment of sugarcane bagasse is a potential substrate for multiple purposes due to the high concentration of residual sugars. Nevertheless, several potentially toxic byproducts are also present. However, a few microorganisms are able to overcome this toxicity by growing on these liquors. Twenty-five filamentous fungi were evaluated in submerged cultivation, but none was able to grow using liquor at a concentration of 100% as the liquid medium. However, six fungi were selected for enzyme induction after being grown in diluted liquor at 50% (v/v) using two feed pulses. Induction experiments were performed using 1% untreated and pretreated sugarcane bagasse. FPase and xylanase activities were detected for all six fungi in submerged cultivation, whereas β-glucosidase was observed in four fungi. The highest xylanase activity (28.8 IU mL−1) was at 72 h for T. harzianum P49P11 using pretreated-SCB as an inducer. This work showed a successful alternative for the final destination of liquor residue as substrate for fungi cultivation prior to enzyme production.